Decolonizing Educational Assessment Ontario Elementary Students and the EQAO - Eizadirad, Ardavan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines the history of standardized testing in Ontario leading to the current context and its impact on racialized identities, particularly on Grade 3 students, parents, and educators. Using a theoretical argument supplemented with statistical trends, the author illuminates how EQAO tests are culturally and racially biased and promote a Eurocentric curriculum and way of life privileging white students and those from higher socio-economic status. This book spurs readers to further question the use of EQAO standardized testing and challenges us to consider alternative models which serve the needs of all students. .
1. My Spiritual Journey as an Educator -- 2. Elementary Standardized Testing on the Bubble: To Eliminate or Maintain? -- 3. Royal Commission on Learning and the Birth of EQAO and the Accountability Movement in Ontario -- 4. Inequality of Opportunity: Experiences of Racialized and Minoritized Students -- 5. Symbiotic Relationship Between Curriculum, Tyler Rationale, and EQAO Standardized Testing -- 6. EQAO Results and School Rankings -- 7. Understanding the Research Approach and the Data -- 8. Invisible Scars and Traumatizing Effects of Standardized Testing: Voices of Grade 3 Children, Parents, and Educators -- 9. External Assessment as Stereotyping -- 10. Decolonizing Educational Assessment Models. .
Keywords: Assessment; Child development; Social justice; Human rights; Educational sociology; Assessment, Testing and Evaluation; Early Childhood Education; Social Justice, Equality and Human Rights; Ethnicity in Education